Strengthening Intraframework Interaction within Flexible MOFs Demonstrates Simultaneous Sieving Acetylene from Ethylene and Carbon Dioxide - Fang Zheng; Rundao Chen; Ying Liu; Qiwei Yang; Zhiguo Zhang; Yiwen Yang; Qilong Ren; Zongbi Bao (Advanced Science, 2023)
Abstract Efficient separation of acetylene (C2H2)/ethylene (C2H4) and acetylene/carbon dioxide (CO2) by adsorption is an industrially promising process, but adsorbents capable of simultaneously capturing trace acetylene from ethylene and carbon dioxide are scarce. Herein, a gate‐opening effect on three isomorphous flexible metal–organic frameworks (MOFs) named Co(4‐DPDS)2MO4 (M = Cr, Mo, W; 4‐DPDS = 4,4‐dipyridyldisulfide) is modulated by anion pillars substitution. The shortest CrO42− strengthens intraframework hydrogen bonding and thus blocks structural transformation after activation, striking a good balance among working capacity, separation selectivity, and trace impurity removal of flexible MOFs out of nearly C2H2/C2H4 and C2H2/CO2 molecular sieving. The exceptional separation performance of Co(4‐DPDS)2CrO4 is confirmed by dynamic breakthrough experiments. It reveals the specific threshold pressures control in anion‐pillared flexible materials enabled elimination of the impurity leakage to realize high purity products through precise control of the intraframework interaction. The adsorption mechanism and multimode structural transformation property are revealed by both calculations and crystallography studies. This work demonstrates the feasibility of modulating flexibility for controlling gate‐opening effect, especially for some cases of significant aperture shrinkage after activation.